EXPLORING THE EVOLUTION OF SOCIAL LOAFING RESEARCH: A BIBLIOMETRIC PERSPECTIVE (Journal of Business Management and Accounting, 2025)
This study explores various aspects of current social loafing research by sampling and analyzing behavioral science publications. This study used bibliographic analysis to examine publications on social loafing in the Scopus database from 1991 to 2023. Analysis includes co-occurrence, coauthorship, visualization, and bibliographic binding. The research findings highlight the most important studies, research topics, and citations in the field of social loafing. Results also highlight important authors, sources/journals, and top keywords. Two of the most influential authors are Williams K.D. and Karau S.J. The focus of their research has been the conceptualization of group dynamics, organizational behavior, and social loafing behavior. This study not only reveals a wide range of research interests, but also highlights the top keywords and the complexity and scope of the concept of social loafing. First, this is the first study to map an organized conceptual structure using bibliographic visualization techniques and represents the first detailed bibliographic analysis of the social loafing literature. The results provide insights into research trends, sources and publications, notable authors, and research topics, helping researchers identify gaps and future directions in the field of social loafing research. The results may facilitate the development and application of social loafing theory to improve team performance and organizational outcomes.